Bacterial genomic epidemiology, from local outbreak characterization to species-history reconstruction. (3rd October 2015) - Gaiarsa, Stefano; De Marco, Leone; Comandatore, Francesco; Marone, Piero; Bandi, Claudio; Sassera, Davide
Abstract : Bacteriology has embraced the next-generation sequencing revolution, swiftly moving from the time of single genome sequencing to the age of genomic epidemiology. Hundreds and now even thousands of genomes are being sequenced for single bacterial species, allowing unprecedented levels of resolution and insight in the evolution and epidemic diffusion of the main bacterial pathogens. Here, we present a review of some of the most recent and groundbreaking studies in this field.